Guidelines for managing diabetes in Ramadan. Issue 10 (25th February 2016) - Ali, S.; Davies, M. J.; Brady, E. M.; Gray, L. J.; Khunti, K.; Beshyah, S. A.; Hanif, W.
Abstract: Background: Globally there are approximately 90 million Muslims with diabetes of which approximately 400 000 reside within the UK. The holy month of Ramadan is a fundamental practice of this religion of which fasting from sun‐rise to sun‐set is an integral part. This poses many potential risks for those with diabetes who wish to observe Ramadan. Methods: The evidence base for best clinical management of Type 1 and Type 2 diabetes during Ramadan was reviewed. We reviewed current and previous recommendations for safe fasting during Ramadan. Results: The risks associated with fasting in those with diabetes and preparing your patient for Ramadan are discussed. We have reviewed the evidence around diet‐controlled diabetes and therapies including; metformin, acarbose, metglitinides, sulfonylureas, thiazolidinidiones, dipeptidyl peptidase‐4 inhibitor (DPP‐4), sodium glucose co‐transporter ‐2 (SGLT‐2) inhibitors, glucagon‐like peptide ‐1 (GLP‐1) receptor agonists and insulin. Conclusion: Up to date guidelines for the management of treatment regimes are set‐out for those with Type 1 and Type 2 diabetes who wish to fast during Ramadan.